(untitled) (Research, Society and Development, 2023)
Congenital syphilis (CS) is one of the most serious preventable adverse outcomes of pregnancy. The objective of this study was to carry out a descriptive temporal analysis of the follow-up of children with early CS in northeastern Brazil between 2010 and 2020. Study carried out in a Philanthropic Maternity Hospital in Aracaju SE, between 2010 and 2020 (subdivided into 2010-2014 | 2015-2020) through analysis of physical records of newborns (NB) with CS. In both periods, most mothers, multiparous (56.3% | 92.2%), with no history of abortion (63.7% | 76.5%) were adequately treated (72.2% | 75.5% ) with negative VDRL (90.2% | 100%). Between 2015 and 2020, there was an improvement in the level of maternal education (48.8%), prenatal care (58.4%) and adherence to partner treatment (44.1%) compared to the previous period. As for the newborns, in both periods the majority had a birth weight greater than 2500g (84.4% | 90.3%), positive VDRL in peripheral blood (70.4% | 76.7%) and non-reactive in the CSF ( 2.2% | 2.2%); in both periods, it was also evidenced that a minority had alterations in the hearing screening (1.1% | 5.4%) and fundoscopy (1.1% | 0.6%), but on long bone radiography between 2010-2014, 8 .5% changed and between 2015-2020 there was an increase to 47.3%. It is concluded that the expansion and improvement of prenatal care, development and improvement of diagnostic and therapeutic technologies, have the power to make CS control an ever closer scenario.